Drug Resistance Assessment Following Administration of Respiratory Syncytial Virus (RSV) Fusion Inhibitor Presatovir to Participants Experimentally Infected With RSV. (11th February 2020) - Stray, Kirsten; Perron, Michel; Porter, Danielle P; Anderson, Francisco; Lewis, Sandra A; Perry, Jason; Miller, Michael; Cihlar, Tomas; DeVincenzo, John; Chien, Jason W; Jordan, Robert
Abstract: Background: Presatovir is an oral respiratory syncytial virus (RSV) fusion inhibitor targeting RSV F protein. In a double-blind, placebo-controlled study in healthy adults experimentally infected with RSV (Memphis-37b), presatovir significantly reduced viral load and clinical disease severity in a dose-dependent manner. Methods: Viral RNA from nasal wash samples was amplified and the F gene sequenced to monitor presatovir resistance. Effects of identified amino acid substitutions on in vitro susceptibility to presatovir, viral fitness, and clinical outcome were assessed. Results: Twenty-eight treatment-emergent F substitutions were identified. Of these, 26 were tested in vitro; 2 were not due to lack of recombinant virus recovery. Ten substitutions did not affect presatovir susceptibility, and 16 substitutions reduced RSV susceptibility to presatovir (2.9- to 410-fold). No substitutions altered RSV susceptibility to palivizumab or ribavirin. Frequency of phenotypically resistant substitutions was higher with regimens containing lower presatovir dose and shorter treatment duration. Participants with phenotypic presatovir resistance had significantly higher nasal viral load area under the curve relative to those without, but substitutions did not significantly affect peak viral load or clinical manifestations of RSV disease. Conclusions: Emergence of presatovir-resistant RSV occurred during therapy but did not significantly affect clinical efficacy in participants with experimental RSV infection. Abstract : Presatovir is an oral respiratory syncytial virus (RSV) fusion inhibitor. In this analysis of a double-blind, placebo-controlled study in healthy adults experimentally infected with RSV, emergence of presatovir-resistant RSV occurred during therapy but did not significantly affect clinical efficacy.